Orexin-A CSF levels correlate with anxiety but not excessive daytime sleepiness in chronic migraine - Peres, Mario Fernando Prieto; Vieira, Domingos Savio; Masruha, Marcelo Rodrigues; Gonçalves, André Leite; Mercante, Juliane Prieto Peres; Naffah-Mazzacoratti, Maria da Graça (Headache Medicine, 2011)
Background: The hypothalamus is a key brain region in the control of energy metabolism, sleep and circadian rhythms, stress and anxiety, food intake, sexual and reproductive behaviors. Orexin-A (hypocretin-1) is a neuropeptide, synthesized in the hypothalamus extensively linked to sleep/wake states, particularly excessive daytime sleepiness. Chronic migraine is comorbid with several conditions but little is known about its mechanisms. We aimed to study the role of orexin-A in the mechanism of chronic migraine and comorbid conditions. Methods: We studied orexin-A levels in the CSF of 60 chronic migraine patients, comparing with age and sex matched controls, and comorbidity with anxiety, depression and excessive daytime sleepiness, using appropriate scales. Results: Orexin-A levels were inversively correlated with anxiety levels (r=-308, p=0,03), but not depression and excessive daytime sleepiness. Orexin levels in CM patients were not different than controls. Discussion/Conclusion: Anxiety in CM may be due to a decrease in orexin-A or may be the cause of its depletion. The orexinergic system may be implicated in anxiety comorbid with migraine.